Patients with Blunt Head Trauma on Anticoagulation and Antiplatelet Medications: Can They be Safely Discharged after a Normal Initial Cranial Computed Tomography Scan?. Issue 6 (June 2014) - Docimo, Salvatore; Demin, Aleksandr; Vinces, Fausto
The literature reports delayed intracranial hemorrhage (ICH) after blunt trauma in patients taking preinjury anticoagulant and antiplatelet (AC/AP) medications. We sought to evaluate the incidence of delayed ICH at our institution and hypothesize that patients taking AC/AP medications who are found to have a negative first computed tomography (CT) scan will not require a second CT scan. A total of 303 patients were retrospectively reviewed. Age, gender, mechanism of injury, international normalized ratio (INR), initial and secondary cranial CT findings, and outcomes were recorded. One hundred sixty-eight (55.4%) were found to be taking AP/AC medications. Ninety-six (57%) were male and 72 (43%) female. Aspirin use was 42.8 per cent (72 of 168), clopidogrel next (39 of 168 [23.0%]), and warfarin least (18 of 168 [10.7%]). One hundred sixty-six (98.8%) presented with significant findings on the first CT scan. Fourteen (87.5%) of the 16 patients with an INR 2.0 or higher presented with an ICH on the first CT. Ninety percent of patients with an INR 1.5 or higher presented with positive findings on the first CT scan. One hundred per cent of patients with an INR 3.0 or higher presented with an ICH on the first CT scan. The incidence of a delayed ICH was two of 168 (1.19%). Of those two patients with a delayed ICH, 100 per cent were taking warfarin and had an INR greater than 2.0. The incidence of delayed ICH was 1.19 per cent. The protocol requiring a second CT scan for all patients on AC/AP medications after a negative first CT scan should be questioned. For patients with blunt head trauma taking warfarin or a warfarin–aspirin combination, a repeat cranial CT scan after a negative initial CT is acceptable. For patients taking clopidogrel, a period of observation may be warranted.